The Effectiveness of Hypertension Exercise, Brisk Walking, and Handgrip Interventions on Blood Pressure Reduction in Hypertensive Patients: A Literature Review - Lisa Isdaryanti; Andri Setiya Wahyudi; Ni Ketut Alit Armini (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hypertension is a major noncommunicable disease that requires effective nonpharmacological interventions, where its management depends not only on pharmacological therapy but also on regular physical exercise. The combination of hypertension exercises, brisk walking, and handgrip exercises has the potential to lower blood pressure through increased cardiorespiratory capacity and vascular vasodilation. This literature review aims to analyze the effectiveness of these interventions, both individually and in combination, and to develop evidence-based recommendations for the management of hypertension. This literature review was conducted to analyze the effectiveness of physical exercise interventions, namely hypertension exercises, brisk walking, and handgrip exercises, on blood pressure reduction and to develop evidence-based recommendations for hypertension management. The study was conducted systematically following the PRISMA guidelines, with articles searched in four electronic databases (PubMed, Scopus, ScienceDirect, Google Scholar) for the period 2020–2025 using keywords related to hypertension, hypertension exercises, brisk walking, handgrip exercises, and randomized controlled trials. Of the 520 articles found, 35 studies met the inclusion criteria (experimental, quasi-experimental, RCT) and were reviewed narratively by category based on exercise type, duration, intensity, and blood pressure outcome. The results of the study were reviewed using a narrative analysis method, which included a thematic synthesis of findings or main categorization based on study variables, referring to PICOS to ensure that the review was targeted at the research objectives. The results of the review show that hypertension exercise, brisk walking, and handgrip exercise interventions, either alone or in combination, are effective in lowering blood pressure with varying durations and intensities depending on the population. The main categories include: 1) Effectiveness of Combination vs. Single: Combined exercises (such as brisk walking and handgrip) are more effective at lowering blood pressure and improving fitness than single exercises. 2) Biological Mechanisms: Blood pressure reduction occurs through improved endothelial function, vasodilation, and sympathetic-parasympathetic nervous system regulation as a result of regular physical exercise. 3) Adherence & Structured Programs: Adherence increases with combination programs and education, resulting in more optimal BP reduction in patients who are consistent and educated. 4) Psychosocial Impact: Combination physical exercise improves quality of life, reduces depression and anxiety, and brings psychosocial benefits to hypertensive patients. Hypertension exercises, brisk walking, and handgrip exercises are effective nonpharmacological interventions for lowering blood pressure in patients with hypertension, with the combination providing more optimal synergistic benefits for long-term compliance.